Inovação e internacionalização em empresas da Indústria Brasileira de Software e Serviços de TI (IBSS) - Sartori, Priscila Pagliarini (Universidade do Vale do Rio dos Sinos, 2015)
The analysis of the behavior of companies in the current competitive scenario highlights the themes of internationalization and innovation as determinants of both the strategies adopted and the performance achieved (RIBEIRO et al., 2010). The objective of this study focuses on the comprehension of the relation between the innovation and internationalization in Brazilian Software Industry and IT Services (IBSS) companies. The research proposal began from the need of an initial understanding of the dynamics of the IT industry and IBSS thus presented a characterization of the sector, industry and business observed in the survey. Characteristics of the innovation process and the internationalization of companies participating in the research are presented as well. Evidences were identified based on the literature review of innovation and internationalization, which were verified empirically, through a multiple case study on how they relate to innovation and internationalization in the background of the four companies analyzed. The analysis of the relationship between innovation and internationalization of companies of this industry was based on information obtained through secondary data and in-depth interviews in a qualitative approach. It was observed in the analyzed cases that innovation is essentially incrementally, focusing on core business, and as an endogenous process, strongly based on human resources. The innovation showed up here as a central element in maintaining competitiveness in both domestic and international markets. The internationalization showed up as a business expansion alternative, but face to the current economic environment it became a part of the strategy of companies. To analyze aspects related to the competitiveness of the companies it was used the perspective of dynamic capabilities (TEECE et al., 1997; TEECE, 2007), allowing the identification of evidences to its ability to adapt to the quick changing environment and the interaction with the ecosystem of the IT industry at the global level to identify and explore new opportunities. Overall, a positive interaction was observed between innovation and internationalization in the context of the analyzed companies, impacting on performance, growth and new business opportunities.
Keywords: Inovação; Internacionalização; Capacidades dinâmicas; Setor de TI; Indústria de software e serviços de TI; Innovation; Internationalization; Dynamic capabilities; IT sector; Software industry and IT services; ACCNPQ::Ciências Sociais Aplicadas::Administração